2020
DOI: 10.1002/adfm.202003512
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Preparation of Biocompatible Gold Nanoplates with Controlled Thickness and Adjustable Optical Properties for Plasmon‐Based Applications

Abstract: The ability to synthesize plasmonic nanomaterials with well-defined structures and tailorable size is crucial for exploring their potential applications. Gold nanoplates (AuNPLs) exhibit appealing structural and optical properties, yet their applications are limited by difficulties in thickness control. Other challenges include a narrow range of tunability in size and surface plasmon resonance, combined with a synthesis conventionally involving cytotoxic cetyltrimethylammonium (CTA) halide surfactant. Here, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Most far‐field optical spectroscopy studies of hexagonal Au NPLs supported on substrates have observed only two major peaks, namely the “dipolar” and “quadrupolar” modes that are mainly concentrated at the vertices and corners. [ 8,11 ] However, our results unambiguously demonstrate the spatial distribution of four LSPR modes at the nanoscale, with spectral components α, β, γ, and δ localized at the vertices (Figure 3c), corners (Figure 3d), side edges (Figure 3e), and faces (Figure 3f) of a single hexagonal Au NPL, respectively. The maxima of the EELS‐LSPR maps at a given resonance frequency (1.20, 1.60, 2.05, and 2.30 eV, respectively) correspond to probe positions at which an Eigen mode is excited and the local electric field is at a maximum.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Most far‐field optical spectroscopy studies of hexagonal Au NPLs supported on substrates have observed only two major peaks, namely the “dipolar” and “quadrupolar” modes that are mainly concentrated at the vertices and corners. [ 8,11 ] However, our results unambiguously demonstrate the spatial distribution of four LSPR modes at the nanoscale, with spectral components α, β, γ, and δ localized at the vertices (Figure 3c), corners (Figure 3d), side edges (Figure 3e), and faces (Figure 3f) of a single hexagonal Au NPL, respectively. The maxima of the EELS‐LSPR maps at a given resonance frequency (1.20, 1.60, 2.05, and 2.30 eV, respectively) correspond to probe positions at which an Eigen mode is excited and the local electric field is at a maximum.…”
Section: Resultssupporting
confidence: 53%
“…Among the NPLs, anisotropic hexagonal Au NPLs are the most intriguing because they give rise to unusual electromagnetic field enhancement, especially at the vertices and corners, [ 5 ] and exhibit low plasmon damping owing to their low surface roughness. [ 6–8 ] Moreover, hexagonal Au NPLs, especially with those elongated shapes, exhibit multiple surface plasmon resonance (SPR) modes, and their refractive index sensitivity is higher than that of Au nanobipyramids and triangular Au NPLs. [ 5 ] A recent study [ 9 ] demonstrated that the electromagnetic field enhancement of hexagonal Au NPLs was strongly dependent on their thickness and lateral size.…”
Section: Introductionmentioning
confidence: 99%
“…This one-step method is simple and highly reproducible; however, it has several drawbacks, namely, the generated particles are mostly spherical with the size ranging between 10 and 30 nm. To synthesize larger (or smaller, sub-10 nm) spherical particles and other shapes (rod, triangle, truncated triangle, and hexagon in 2D and polyhedral shapesdecahedron, icosahedron, and tetrahedronin 3D) additional growing steps (seed-mediated growth) and/or the usage of additives (e.g., surfactants, macromolecules) are needed. These additives adsorbing onto the specific crystal plain inhibit the further crystal growth in this direction, thus the growth occurs along preferential crystal plains producing various nonspherical structures. Surfactants such as cetyltrimethyl­ammonium bromide (CTAB) and cetyltrimethyl­ammonium chloride (CTAC) adsorb on the lowest energy {111} facets and suppress their growth, which in turn directs and promotes the evolution of nanoplates. , Usually to synthesize nanoplates with a size greater than 100 nm, seed-mediated growth methods have been used. , Besides, one-step photochemical reduction methods were also proposed in the literature. , Generating both spherical nanoparticles and micrometer-sized nanoplates in a predictable size in a one-step method is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, a facile synthesis of 2D Au nanocrystals with around 10 nm in thickness, tunable lateral size, and surface morphology in the aqueous phase is reported. Unlike Au nanoplates/nanoprisms in the form of well-defined triangles or hexagons documented in previous studies, the current products exhibit fruitful presence of wrinkles, random in-plane branches or holes, and wavy edges. By conducting the reaction at room temperature and in ice–water bath, respectively, crumpled and flat Au nanosheets could be selectively obtained in high purity, respectively.…”
Section: Introductionmentioning
confidence: 65%